Identification and Root Cause Analysis of the Key Bottlenecks Affecting the Lead Time of Factory Acceptance Testing of Large Bore Engines - Rantanen, Atte (My University, 2026)
This thesis investigated the root causes of delays in the factory acceptance testing (FAT) process at a company manufacturing large engines. The objective was to identify why engines experience extended lead times during these tests and to propose improvements that could increase the throughput capacity of existing test cells infrastructure. The study followed a mixed methods approach within a case study design, combining quantitative data analysis with qualitative interviews, hands-on training sessions at the factory, and a questionnaire. Root cause analysis was conducted using Fishbone and Five Why’s methods. The quantitative analysis established that the LB3 engine represented the most significant bottleneck in testing and revealed through Pareto analysis that five issue categories – tightening errors, installation errors, pipe tightening errors, missing parts, and supplier quality – accounted for approximately 80% of all categorized problems. The root cause analysis traced these issues back to an incorrect assembly order in the company’s manufacturing control system, insufficient tightening procedures for pipe fittings and tight installation clearances in the engine design. The questionnaire validated these findings, with the majority of respondents confirming that unclear tightening procedure and part reinstallations caused by incorrect assembly order are the most significant factors contributing to leaking connections. The study concluded that assembly work is the largest source of issues encountered during FAT. However, the errors are not caused by a lack of care from the workers but are enabled by systemic factors such as incorrect assembly instructions leading to unnecessary part reinstallations and tight installation clearances. Two main proposals were made: correcting the assembly order in the manufacturing control system and ensuring correct installation methods for the pipe fittings through training. These changes would target the identified root causes and deliver improvements in FAT lead time and lead time variation.
Keywords: root cause analysis; factory acceptance test; Pareto analysis; data analysis; questionnaire; lead time; Five Why’s; large bore engine